Is early diagnose for Vitamin A deficiency better than the current supplementation programme of Nepal? - Simkhada, Padam; Sathian, Brijesh; Adhikari, Sudhir; van Teijlingen, Edwin R; Roy, Bedanta (Journal of Biomedical Sciences, 2016)
Journal of Biomedical Sciences 2015, 2(4):28-30